Fundamental Factor Analysıs Of Systematıc Rısk Fundamental Analysıs Of The Lq-45 Stock Index, Whıch Lısted On The Indonesıa Stock Exchanges - Erawati Kartika; Rini Elfina; Sumardin Sumardin; Muhammad Sidik; jeffy Mutiara (Cita Konsultindo Research Center, 2023)
The purpose of the research conducted by researchers is to determine the effect of fundamental factors on systematic risk in listed companies on Stock Indices LQ 45 on the Indonesia Stock Exchange. Fundamental factors are proxied by the Current Ratio, Return On Assets (ROA), and Debt to Equity Ratio (DER), while systematic risk is proxied by stock beta. The period carried out was in the 2016-2018 period. The research population is all companies included in the LQ 45 Stock Index on the Indonesia Stock Exchange for the period 2016 -2018. Samples obtained using purposive sampling technique consisting of 18 companies. The data analysis technique used is multiple linear regression. Based on the results of data analysis, the Current Ratio has no significant effect on Systematic Risk with a regression coefficient of -0,003 and a significance value of 0,202. The variable Return On Assets (ROA) has no significant effect on Systematic Risk with a regression coefficient value of -0,006 and a significance value of 0.831. Variable Debt to Equity Ratio ( DER ) has no significant effect on Systematic Risk with a regression coefficient of 0,047 and a significance value of 0,184. The F test value shows that the fundamental factor variables are proxied by the Current Ratio , Return On Assets (ROA), and Debt to Equity R atio ( DER ) has no effect on Systematic Risk because the significance value is more than 0,05 which is 0,795 . The adjusted R2 value of 0,046 indicates that the predictive ability of the 3 independent variables is 4,6 % and the remaining 95,4 % is influenced by other variables outside the model. .